Minecrafters: An educational model for developing collaboration - Hughes, Janette; Morrison, Laura; Butler-Ulrich, Tess; Robb, Jennifer (Proceedings of the International Conference on Networked Learning, 2024)
In response to significant global events such as the COVID-19 pandemic, educational environments are undergoing a fundamental transformation towards collaborative online spaces and networked learning. Networked learning includes (a) the process of learning with and through other people and resources and (b) the environment (i.e., the internet) and platforms (i.e., YouTube, websites, social media, discussion forums) that support these connections or networks (Hodgson & McConnell, 2019). This shift in how learning is done necessitates a reevaluation of pedagogical methods to foster the development of students' global skills and competencies. These competencies, as defined by the Council of Ministers of Education Canada (CMEC), are recognized as essential for individuals to not only adapt but thrive in our current and future world. This world is characterized by unprecedented simultaneous challenges, often referred to as a 'polycrisis,' and rapid advancements in artificial intelligence (A.I.) that have the potential to reshape every aspect of human existence. Therefore, it is imperative that we delve into a deeper investigation and understanding of innovative pedagogical approaches to ensure students are adequately prepared for the evolving landscape. Collaboration is arguably one of the most important of the global skills and competencies as it underpins many of the essential skills youth need to thrive in educational and non-educational settings. More specifically, collaboration underpins the type of networked learning rising in popularity in formal and informal learning settings (Bülow & Nørgård, 2021). As a result, this exploratory research focuses on Minecraft: Education Edition (M:EE) as a tool for developing collaboration through critical making and team-based learning. Over a five-day spring-break camp, two cohorts of students (grades four to six and grades seven to eight) participated in open-ended design-based learning challenges online (in the virtual meeting platform, Google Meet, and in the virtual world, M:EE). Data analysis revealed that collaboration manifested itself in three primary modes: co-constructing knowledge, peer-teaching, and conflict management. Analysis further revealed that younger versus older students build and collaborate in the online environment very differently, which at times mirrored the 'real world' classroom. These findings have implications for designing age-appropriate online learning experiences to support collaboration in a networked environment, especially within virtual simulation and creation worlds like Minecraft.